Phenolic Profile and Antioxidant Activity of Selected Premium Wines from Herzegovina Region - Kazazić, Maja; Marino, Chiara; Mehić, Emina (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2025)
Red wines are rich in antioxidants, which have anti-inflammatory activity and beneficial effect on human health. The aim of this research was to determine the content of bioactive compounds, i.e. total phenols, anthocyanins and tannins, as well as antioxidant activity in red wines from the Herzegovina region. Four wines from two different harvest years, i.e. 2019 and 2021, were analysed. Phenolic compounds are important wine quality parameters that affect color, taste and aroma. The content of total phenols varied from 1733.87 ± 10.22 to 2382.09 ± 21.42 mg GAE/L. The content of total anthocyanins, which directly affect the color of red wines, was determined by the pH differential method and the results obtained ranged from 13.64 ± 0.19 to 21.76 ± 0.35 mg CGE/L. Total tannins were determined using spectrometric method, and values ranged from 9.00 ± 0.09 to 11.42 ± 0.21 g/L. The antioxidant activity was assessed using two different methods, FRAP and ABTS. The total phenolic content of the tested wines was positively correlated with their antioxidant activity. The content of total phenols, anthocyanins, tannins and antioxidant activity were influenced by the year of harvest as well as the aging methods used.